Multiplex immunohistochemical phenotyping of T cells in primary prostate cancer. Issue 6 (21st February 2022) - Ozbek, Busra; Ertunc, Onur; Erickson, Andrew; Vidal, Igor D.; Gomes‐Alexandre, Carolina; Guner, Gunes; Hicks, Jessica L.; Jones, Tracy; Taube, Janis M.; Sfanos, Karen S.; Yegnasubramanian, Srinivasan; De Marzo, Angelo M.
Abstract: Background: Most prostate cancers are "immune cold" and poorly responsive to immune checkpoint inhibitors. However, the mechanisms responsible for the lack of a robust antitumor adaptive immune response in the prostate are poorly understood, which hinders the development of novel immunotherapeutic approaches. Aims: Most inflammatory infiltrates in the prostate are centered around benign glands and stroma, which can confound the molecular characterization of the antitumor immune response. We sought to analytically validate a chromogenic‐based multiplex immunohistochemistry (IHC) approach applicable to whole slide digital image analysis to quantify T cell subsets from the tumor microenvironment of primary prostatic adenocarcinomas. As an initial application, we tested the hypothesis that PTEN loss leads to an altered antitumor immune response by comparing matched regions of tumors within the same individual with and without PTEN loss. Materials & Methods: Using the HALO Image Analysis Platform (Indica Labs), we trained a classifier to quantify the densities of eight T cell phenotypes separately in the tumor epithelial and stromal subcompartments. Results: The iterative chromogenic approach using 7 different antibodies on the same slide provides highly similar findings to results using individually stained slides with single antibodies. Our main findings in carcinomas (benign removed) include the following: i) CD4+ T cells are present at higher density than CD8+ T cells; ii) all T cell subsets are present at higher densities in the stromal compartment compared to the epithelial tumor compartment; iii) most CD4+ and CD8+ T cells are PD1+; iv) cancer foci with PTEN loss harbored increased numbers of T cells compared to regions without PTEN loss, in both stromal and epithelial compartments; and v) the increases in T cells in PTEN loss regions were associated with ERG gene fusion status. Discussion: This modular approach can apply to any IHC‐validated antibody combination and sets the groundwork for more detailed spatial analyses. Conclusion: Iterative chromogenic IHC can be used for whole slide analysis of prostate tissue samples and can complement transcriptomic results including those using single cell and spatial genomic approaches.